Avaliação do perfil da resposta imune inata em pacientes infectados pelo vírus Chikungunya - Moizeis, Raíza Nara Cunha (2018)
Chikungunya virus infection cause high morbidity mainly due to arthalgia and arthritis generated. An inflammation induced in the joints by viral infection involve innate and adaptive immunity. However, the immunological mechanisms involved in protection or pathogenesis have not yet been completely elucidated. Thus the aim of the present study was to evaluate the expression of innate immunity receptors and cytokines induced by their activation in patients infected with the Chikungunya virus. In this study the expression of mRNA by real-time PCR of Toll receptors (TLR3, TLR7, TLR8, TLR9), RLR (MDA5 and RIG-1), adaptive molecules (TRIF and MyD88) and cytokines (IFN-α, IFN-β, IFN-γ, IL-6, IL-12 and TNF-α) in whole blood of patients in the acute phase of the Chikungunya infection (N=28). Uninfected cases (N=9) were used as negative controls. Pacients infected with CHIKV are older than TLR3 mRNA expression in relation to healthy languages. Influences of the expression of TLR7, TLR9, MDA5 and RIG-1 in CHIKV infected patients in the past have not been confirmed but have been shown to decrease TLR8 mRNA expression when they were found in the healthy populations. Factors related to CHIKV infection in pacients in the suck phase, infection with IFN-α, IFN-γ and IL-6, infections of innate immunity with antiviral action, recognition of the virus by TLR3 and to a lesser extent by MDA5 and RIG-1, in addition to mechanisms that possibly involve TLR9 collaboration. Furthermore, positive correlations were found between the mRNA expression of TLR3, TLR7, TLR9, MDA5 and RIG-1 with IFN-α expression. Interestingly, positive correlations between TLR3 mRNA expression with IFN-α, IFN-γ and IL-12 were also observed, and between MDA5 mRNA expression with IFN-α, IFN-γ and IL-12 were also observed, and between MDA5 mRNA expression with IFN-α, IFN-β, IFN-γ and IL-6, IL-12 and TNF-α.